Efeitos biológicos do tratamento de condicionamento radicular em dentes afetados periodontalmente - análise in vitro - Silva, Aline Cristina (2013)
The objective of this study was to evaluate the root surfaces modifications after the application of different chemicals agents, and their influence on the attachment of a fibrin network and fibroblasts. From 96 anterior mandibular human incisor teeth, extracted due to severe periodontal disease, were obtained 192 dentin blocks (3x3x1 mm) of buccal and lingual surface and randomly divided into 6 groups: Control- control group, which received no treatment; Root surface scaling and root planing (SRP) - root surface was scaling and root planning with Gracey curetes; Citric acid - SRP + 30% citric acid 5 min; EDTA (ethylenediaminetetraacetic acid) - SRP + 24% EDTA gel for 1 min; Tetracycline capsule - SRP + for 3 min with a solution obtained by dissolving one 500 mg capsule of tetracycline in 2 mL of saline solution; Tetracycline gel - SRP + 50 g/mL tetracycline gel for 1 min. After dentin treatment the specimens were analyzed using 4 methodologies: 1- the demineralization level and residues of the product (n = 9); 2- the adhesion of blood components after 20 min of surface treatment (n = 9); 3- the fibroblast attachment after 24h (n = 9), were analyzed by scanning electron microscopy (SEM); and 4- the cell metabolism after 4h (n = 5) the methyltetrazolium (MTT) assay was used. Citric acid, EDTA and Tetracycline gel removed completely smear layer and smear plug on root surface, resulted in adequate demineralization .Tetracycline capsule produced great tetracycline residues with several demineralization areas on root dentin surface. Tetracycline gel and EDTA groups had more fibroblast fixation than other experimental groups. The highest mean blood clot adhesion score was observed in roots treated with a tetracycline gel, whereas, the least score was observed in roots treated with tetracycline capsule. These results demonstrated that EDTA and Tetracycline gel surface demineralization removed the smear layer over dentin surface and promoted adhesion of a fibrin network and fibroblast cells attachment. The Tetracycline capsule demonstrated less effective performance in all parameters tested.